THREAT IS VIRUS NOT THE PEOPLE: FEAR OF COVID-19, DEPRESSION AND SELF-CONTROL - Saba Ahmed; Hamid Waqas; Muhammad Awais-E-Yazdan; Seemab Chaman (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The coronavirus (COVID-19) pandemic outbreak has a significant influence on both peoples’ physical and psychological health. Healthcare workers remained most vulnerable to COVID-19 due to requirement of their job. The current study examines terror of COVID-19 and depression along with self-control among the nurses in Pakistan. The cross-sectional study design was employed and data was collected from a sample of nurses from the hospitals of Rawalpindi and Islamabad using non-probability convenience sampling technique. The inclusion criteria involve nurses as they had direct contact with COVID-19 patients for their treatment. The statistical tool of Smart PLS was used for model assessment and regression analysis. Results revealed significant relationship between fear of COVID-19 and depression among nurses. Moreover, self-control also significantly moderated the association between distress of COVID-19 and depression. Future work can be carried on other stressor and psychological factors. Furthermore, there is a need to investigate the vaccination attitude in the future since due to misconception and minimal information available regarding the COVID-19 vaccine.